BikeScienceWeb: a tool for bicycle-related urban planning - Pena, Thiago J.B.; de Souza, Higor A. [UNESP]; Lemos, Letícia L.; Kon, Fabio (My University, 2023)
BikeScienceWeb is a data science tool containing analytic resources for active urban mobility planning. The tool aims to enable specialists to carry out their analyses without the need for programming knowledge. BikeScienceWeb can be used to include and exclude layers of subject-related geolocation information, import custom layers, compare two maps with different scenarios, and evaluate bicycle travel flows using travel survey data. The tool is available for use at the São Paulo Traffic Engineering Company (CET) and for the general public. A survey carried out with specialists in urban mobility showed that 70% deemed the tool as easy to use, 76% deemed it as useful for planning active mobility, and 88% had an intention to use the tool for their activities.